Halal Labels and Religious Commitment: Their Impact on Bottled Water Purchases - Putri, Rizky Nur Ayuningtyas (Profesional Muda Cendekia Publishing, 2024)
Research Aims: To determine how halal labelling affects purchasing decisions for bottled drinking water products among Muslim students in Solo Design/methodology/approach: The study used quantitative descriptive analysis with primary data. The data analysis method used multiple linear regression analysis with independent variables, namely halal labelling (X1) and religiosity (X2). The number of samples in the study was 183 respondents. This study uses a purposive sampling technique with specific criteria. The study's dependent variable (Y) is the decision to purchase bottled drinking water Research Findings: halal labelling and religiosity have a positive and significant effect on customer decisions to buy bottled mineral water drinks. The value of the coefficient of determination concluded that the contribution of the independent variables in the regression model can explain the variation of the dependent variable by 48,6%. In contrast, the rest is explained by other variables outside the regression equation model. Based on the analysis results, actual steps need to follow up on purchasing decisions for halal bottled drinking water products, one of which is that the university can provide and facilitate the availability of bottled drinking water (AMDK) products on the campus. Besides increasing awareness of halal drinking water, it can also positively impact the development of halal products in universities in Solo. Theoretical Contribution/Originality: The research highlights the simultaneous and partial influence of halal labelling and religiosity on purchasing decisions for bottled drinking water in universities in Solo. This adds a nuanced understanding of consumer behavior in a specific religious and educational context. The study emphasizes the need for further research into the urgency of providing halal AMDK, suggesting that such products are crucial for consumer assurance. This calls attention to a potentially underserved market segment. Keywords: Halal Label, Religiosity, Purchase Decision, Bottled Drinking Water.